The provision of complementary therapy on the intensity of pain reduction in childbirth - Rika Agustina; Yunita Anggriani; Inggit Primadevi (Universitas Aisyah Pringsewu, 2023)
Labor pain is a physiological condition that begins to arise in the 1st stage of labor in the latent phase and the longer the pain is felt it will get stronger, the peak of pain occurs in the active phase. The personality of a mother undergoing labor plays an important role in pain, naturally, the mother will feel anxious, tense and weaker in facing labor than a relaxed and confident mother. The study aimed to find out complementary care that can help mothers in reducing labor pain. This research method is a case study followed by continuity of care from pregnant women, childbirth, postpartum and newborns. The intervention was given to 15 pregnant women who were followed until they gave birth. The results of the intervention found that there was a decrease in pain in the birthing mother with the use of a gym ball as seen from the results of the NRS (Numeric Rating scale) there was a decrease in value from 8 (moderate pain) to a value of 4 (no pain). In giving complementary aromatherapy, the mother still feels labor pain but looks more relaxed. Conclusion Complementary administration of lavender aromatherapy can be given simultaneously as gym ball complementary administration helps mothers relax more and makes birth mothers more comfortable. Abstrak: Nyeri persalinan merupakan suatu kondisi yang fisiologis yang mulai timbul pada persalinan kala 1 fase laten dan semakin lama nyeri yang dirasakan akan bertambah kuat, puncak nyeri terjadi pada fase aktif. Kepribadian seorang ibu yang sedang menjalani proses persalinan berperan penting terhadap rasa nyeri, secara alamiah ibu akan merasa cemas, tegang dan lebih lemah dalam menghadapi persalinan dibanding ibu yang rileks dan percaya diri. Tujuan penelitian untuk mengetahui asuhan komplementer yang dapat membantu ibu bersalin dalam mengurangi nyeri persalinan. Metode penelitian ini dengan studi kasus yang diikuti secara continuity of care dari ibu hamil, bersalin, nifas dan bayi baru lahir. Di berikan intervensi pada 15 orang ibu hamil yang diikuti sampai bersalin. Hasil intervensi didapatkan adanya penurunan nyeri pada ibu bersalin dengan penggunaan gymball dilihat dari hasil NRS (Numeric Rating scale) terdapat penurunan nilai dari 8 (nyeri sedang) menjadi nilai 4 (tidak nyeri). Pada pemberian komplementer aromatherapi ibu bersalin tetap merasakan nyeri persalinan namun terlihat lebih rileks. Kesimpulan Pemberian komplementer aromatherapi lavender dapat diberikan bersamaan saat pemberian komplementer gymball membantu ibu lebih rileks dan membuat ibu bersalin lebih nyaman.